2003
DOI: 10.2119/2003-00011.zingarelli
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Poly(ADP-ribose) polymerase-1 (PARP-1) is activated in response to DNA injury in eukaryotic cells and has been implicated in cell dysfunction in reperfusion injury. In this study we investigated the role of PARP-1 on apoptosis in early myocardial reperfusion injury. Mice genetically deficient of PARP-1 (PARP-1-/-) and wild-type littermates were subjected to myocardial ischemia and reperfusion. Myocardial injury was assessed by measuring the serum levels of creatine phosphokinase and oligonucleosomal DNA fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…3-AB significantly improved the outcome of myocardial dysfunction, as evidenced by a reduction in creatine phosphokinase levels, diminished infarct size, and preserved the ATP pools (Zingarelli et al, 1997). These findings were subsequently confirmed and extended into various other models using PARP inhibitors of increasing selectivity and potency (Thiemermann et al, 1997; Bowes et al, 1998a; Bowes et al, 1998b; Docherty et al, 1999; Liaudet et al, 2001a, Liaudet et al, 2001b, Faro et al, 2002; Zingarelli et al, 2003; Khan et al, 2003; Kaplan et al, 2005; Song et al, 2008; Eltze et al, 2008; Roesner et al, 2010; Zhang et al, 2012). Furthermore, Zingarelli also demonstrated that PARP deficient mice are protected against myocardial reperfusion injury (Zingarelli et al, 1998; Yang et al, 2000).…”
Section: Beyond Anticancer Therapy: Stroke Circulatory Shock Carmentioning
confidence: 70%
“…3-AB significantly improved the outcome of myocardial dysfunction, as evidenced by a reduction in creatine phosphokinase levels, diminished infarct size, and preserved the ATP pools (Zingarelli et al, 1997). These findings were subsequently confirmed and extended into various other models using PARP inhibitors of increasing selectivity and potency (Thiemermann et al, 1997; Bowes et al, 1998a; Bowes et al, 1998b; Docherty et al, 1999; Liaudet et al, 2001a, Liaudet et al, 2001b, Faro et al, 2002; Zingarelli et al, 2003; Khan et al, 2003; Kaplan et al, 2005; Song et al, 2008; Eltze et al, 2008; Roesner et al, 2010; Zhang et al, 2012). Furthermore, Zingarelli also demonstrated that PARP deficient mice are protected against myocardial reperfusion injury (Zingarelli et al, 1998; Yang et al, 2000).…”
Section: Beyond Anticancer Therapy: Stroke Circulatory Shock Carmentioning
confidence: 70%
“…In heart I/R injury the hyper-activation of PARP is able to disturb the energy generation process and the mitochondrial function. PARP can also regulate the expression of various proteins and cytokines such as ICAM-1 [ 28 ], AP-1 complex [ 29 ], nf-kb [ 30 ], TNF-α and IL-10 [ 31 ]. PARP inhibition or PARP deficiency have been shown to suppress the cytokines expression in vitro or in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Ppif −/− mice, which lack the crucial component for MPT­driven regulated necrosis CypD, are protected against cardiac ischaemia–reperfusion injury 259,260 , angiotensin­II­induced cardiomyopathy 261 , and arrhythmia (in this last case, perhaps also linked to preserved Ca 2+ fluxes) 262 . The deletion of Parp1 , which encodes poly(ADP­ribose) polymerase 1 (a nuclear DNA repair enzyme that is required for parthanatos), mediates beneficial effects in mouse models of ischaemia–reperfusion injury 263,264 and atherogenesis 265 . Moreover, both Ripk3 −/− mice (which lack a critical regulator of necroptosis) and mice engineered to overexpress dominant­negative CaMKII in the heart are protected against ischaemia–reperfusion injury and the cardiotoxic effects of doxorubicin 266 .…”
Section: Therapeutic Potential Of Mtasmentioning
confidence: 99%